2016
DOI: 10.1021/jacs.6b10745
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Can Form a Well-Defined Binding Pocket for Hydrocarbons

Abstract: Cytochrome c can acquire peroxidase when it binds to cardiolipin in mitochondrial membranes. The resulting oxygenation of cardiolipin by cytochrome c provides an early signal for the onset of apoptosis. The structure of this enzyme-substrate complex is a matter of considerable debate. We present three structures at 1.7 – 2.0 Å resolution of a domain-swapped dimer of yeast iso-1-cytochrome c with the detergents, CYMAL-5, CYMAL-6 and ω-undecylenyl-β-D-maltopyranoside bound in a channel that places the hydrocarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(88 citation statements)
references
References 79 publications
7
81
0
Order By: Relevance
“…The full results of the survey will be reported in detail elsewhere (e.g. McCelland et al 2016;Silburn et al in prep), and confirmed that the targeted area contained a range of sediment types from sandy muds, through to gravelly sands, reflecting the wider shelf region (For full details, see Online Resource 3). In summary, coarser sediments dominate the central region, and the percentage of fine sediments (median grain size \ 63 lm), which ranges between 1.73 and 86.61% across the entire area, increases towards the Northeast and Southwest corners (Fig.…”
Section: Sediment Classificationsupporting
confidence: 55%
See 1 more Smart Citation
“…The full results of the survey will be reported in detail elsewhere (e.g. McCelland et al 2016;Silburn et al in prep), and confirmed that the targeted area contained a range of sediment types from sandy muds, through to gravelly sands, reflecting the wider shelf region (For full details, see Online Resource 3). In summary, coarser sediments dominate the central region, and the percentage of fine sediments (median grain size \ 63 lm), which ranges between 1.73 and 86.61% across the entire area, increases towards the Northeast and Southwest corners (Fig.…”
Section: Sediment Classificationsupporting
confidence: 55%
“…Sediment versus habitat type While the terms are often used interchangeably, they are commonly closely related (LaFrance et al 2014;Heip et al 1985), and the faunal analysis performed herein shows that sediment size is generally a good predictor of macrobenthic community structure (McCelland et al 2016). It should be noted that considerable overlap occurs in species occurrence between closely related sediment types.…”
Section: Considerations For Data Interpretationmentioning
confidence: 70%
“…On a molecular level, the extended-lipid anchorage model (34) is typically proposed, in which CL binds to cyt c through electrostatic and hydrogen bonding interactions. Recent crystal structures of yeast iso-1–cyt c show that docked linoleic acid interacts with Asn52 and sits adjacent to the Tyr67 and heme (35). Thus, the linoleic acid can interrupt the internal hydrogen bonding network by interactions with either of these residues.…”
mentioning
confidence: 99%
“…The displacement of Ω‐loop D (Gly77 specifically) is highlighted by an arrow while disordered Ω‐loop C is signified by a dashed line. (B) As per A, and including domain‐swapped cyt c (PDB 5klu, red) and Lys73‐ligated cyt c (PDB 4q5p , navy). Residues 83–103 of domain‐swapped cyt c are not shown.…”
Section: Resultsmentioning
confidence: 99%